The Role of Entrepreneurial Marketing in Achieving Competitive Advantage in Micro, Small and Medium Enterprises (MSMEs) - Waris, Abdul; Eko Boedhi Santoso; Fatkhur Rochman; Izzatul Ulya (Jurnal Penelitian, 2025)
The micro, small and medium enterprises (MSMEs) sector continues to drive the national economy as a crucial and strategic sector. Competitive ability is a key factor for companies to succeed and survive in the existing situations and conditions, especially in facing unexpected and rapid business environment changes (environmental dynamics). This research aims to examine how environmental dynamics affect competitive advantage, both directly and through the role of entrepreneurial marketing strategies, among business actors in the Tempe Chips Industry Centre in Sanan, Malang City, as an evaluation for future business development to build competitive advantage in running their business. Explanatory research employs a quantitative methodology, collecting data through questionnaires and analysing it using SmartPLS. The results show that environmental dynamics do not directly affect competitive advantage, but have been proven to influence entrepreneurial marketing strategies, which in turn significantly enhance competitive advantage. This means that the role of entrepreneurial marketing is as a bridge between environmental dynamics and the enhancement of competitive advantage; thus, entrepreneurial marketing becomes an important mediating variable. Thus, in the midst of a dynamic business environment, entrepreneurs need to be more innovative and adaptive to remain competitive.